2015
DOI: 10.17784/mtprehabjournal.2015.13.304
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of low level laser therapy in vitro cultures of bacteria and fungi

Abstract: Background: Low intensity laser therapy has been used to accelerate the ulcers healing due to its healing, anti-inflammatory, analgesic and anti-edematous effects. Contaminations by bacteria or fungi on these ulcers commonly happen, constituting a major complication of healing, but there is no consensus about laser therapy bactericidal or fungicidal effect. Aim: To analyze the effects of different times of appliantion using the 808nm and 660nm lasers on cultures of different bacterial species and fungi in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Another study by Andraus et al has reported that low-level laser therapy (LLLT) with 660nm or 808nm lasers has no bactericidal effect and no hindrance growth in the illuminated region of plates at different irradiation times (2.15 min, 1.7min and 40 seconds) [24]. We hypotheses that the form of prepared bacterial biofilm for irradiation represents a critical factor to observe the effect of LLLT on bacterial growth and its intracellular biomolecules activities.…”
Section: Discussionmentioning
confidence: 73%
“…Another study by Andraus et al has reported that low-level laser therapy (LLLT) with 660nm or 808nm lasers has no bactericidal effect and no hindrance growth in the illuminated region of plates at different irradiation times (2.15 min, 1.7min and 40 seconds) [24]. We hypotheses that the form of prepared bacterial biofilm for irradiation represents a critical factor to observe the effect of LLLT on bacterial growth and its intracellular biomolecules activities.…”
Section: Discussionmentioning
confidence: 73%
“…33 Radiation absorbs chromophores that cause conformational changes in some molecules that produce free radicals, thus triggering disruption or damage to the membranes of bacteria and fungi. 34 On the other hand, some researchers argue that microbial cells are transparent to visible laser light and are not affected by radiation. Sensitizing the cell with a chemical dye before the laser treatment will help absorb the light of the laser wavelength and produce an excited triplet state.…”
Section: Discussionmentioning
confidence: 99%
“…LLLT also has fibrinolytic effects, anti-inflammatory effects that block prostaglandin synthesis, analgesic effects through secreting chemotaxis substances that stimulate endorphin release, and fungicidal and bactericidal effects by increasing the amount of interferon and damaging the cell wall that causes protein denaturation in the cytoplasm. 29,34 The specifications of a laser and the biological parameters of the microorganism affect laser treatment effectiveness. Important laser properties of influence include its wavelength, fluence or dose, irradiance, exposure time, emission mode (continuous or pulse), and number or frequency of exposures.…”
Section: Discussionmentioning
confidence: 99%
“…We think that exposure of microorganisms to low-level laser treatment (LLLT) for an extended period, similar to the case of Chung ̓ s study, leads to a thermal effect instead of photo-biostimulation, and thermal accumulation actively limits the ionization of chromophore in intracellular biomolecules. 27,28 Another study by Andraus et al revealed that LLLT did not have any bactericidal effect with the light of 660 nm or 808 nm and any hindrance to growth in the illuminated region of plates at different irradiation times (2.15 minutes, 1.7 minutes and 40 seconds). 29 We hypothesize that the form of bacterial biofilm prepared for irradiation represents a critical factor in observing the action of LLLT on bacterial growth and its intracellular biomolecules activities.…”
Section: Discussionmentioning
confidence: 99%